The Synergistic Effect of Prototypicality and Authenticity in the Relation Between Leaders’ Biological Gender and Their Organizational Identification - Monzani, Lucas (Journal of business ethics, 2015)
Role congruity theory affirms that female managers face more difficulties at work because of the incongruity between female gender and leadership role expectations. Furthermore, due to this incongruity, it is harder for female managers to perceive themselves as authentic leaders. However, followers’ attributions of prototypicality could attenuate this role incongruity and have implications on a managers’ organizational identification (OID). Hence, we expect male managers to be more authentic and to identify more with their organizations, when compared to female managers who are low in prototypicality. We hypothesized that authentic leadership dimensions mediate the relation between managers’ biological gender and their OID. However, this indirect effect is conditional of these managers' team prototypicality. For testing these hypotheses, we conducted an online experiment with 149 participants (M age = 43.42 years; SD = 11.41; 43 % female) from different work sectors using a 2 (participants’ biological gender) × 2 (team prototypicality: low vs. high) between-subject design. As predicted, men scored higher on authentic leadership, and three dimensions partially mediated the effect of participants’ biological gender on OID. In the low team prototypicality condition female managers scored lower in authentic leadership and identified less with the organization, whereas in the high team prototypicality condition, no gender differences were found.